Guidelines for Best Practice of Augmented Reality in Websites Emphasizing Usability - Souza, Andrea Silva [UNESP]; Marar, Joao Fernando [UNESP]; Paschoarelli, Luiz Carlos [UNESP]; Bidarra, J.; Eca, T.; Tavares, M.; Leote, R.; Pimentel, L.; Carvalho, E.; Figueiredo, M. (Artech-international Assoc, 2015)
This short paper aims to show the beginning of an research on augmented reality (AR) applied in websites, emphasizing usability in data visualization and the intuitive aspects of the interface.
Keywords: augmented reality; interaction; interface; usability; users; websites